Romanian agrifood trade with the Mediterranean countries: From the Barcelona declaration to the Euro-Mediterranean partnership - Camelia Gavrilescu; Nicoleta Mateoc-Sîrb; Teodor Mateoc (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
Romania had important trade relations with the Mediterranean countries since before 1990. Subsequently, in both the pre-accession and post-accession period, this group of countries took together about 47% of the extra-EU Romanian agri-food exports and 16% of the extra-EU imports (averages 2002-2016). On the other hand, the imports of vegetables from the Mediterranean area are severely competing the Romanian domestic production (which is rather large, but is very poorly organized all along the supply chains), while the imports of fruit are competing the EU domestic production and intra-EU trade. The present paper is analyzing the dynamics and changes in competitiveness of the Romanian agri-food trade with the Mediterranean countries, in terms of value and volume, composition by products and partners. The results show a significant increase in the Romanian exports to the Mediterranean countries (which lead to the shift of the country's regional trade balance from negative to positive since 2010), as well as competitiveness gains on the main destinations markets in the region.
Keywords: F14; Q17; 330; agri-food trade; Romania; Euro-Mediterranean Partnership; competitiveness